HUBUNGAN STATUS GIZI DENGAN PRESTASI BELAJAR MAHASISWI KEBIDANAN STIKES DUTA GAMA KLATEN - Putri Kusumawati Priyono; Happy Primariasari (STIKES DUTAGAMA KLATEN, 2019)
Background: Learning achievement is an assessment of the results of business activities that are expressed in the form of symbols, numbers, letters, or sentences that can reflect the results that have been achieved by each student in a certain period. Learning achievement is a thing that cannot be separated from learning activities, because learning activities are processes, while achievement is the result of assessment of the learning process. The results of interviews conducted by STIKES students Duta Gama Klaten found several problems related to physiological conditions. Complaints that are often experienced by students include nutritional disorders which include poor nutritional status until the problem of obesity affects concentration. Purpose: To determine internal physiological factors that are related to student learning achievement in an effort to improve learning achievement and analyze the relationship between nutritional status and learning achievement. Method: Analytical Observational with Cross Sectional method. Result :. the number of respondents is 20, for the nutritional status variable the mean ± SD value is 22.23 ± 4.05, this means that on average respondents have good nutritional status and for the GPA variable it has a mean value of 3.62 ± 0.25 which is with the average value of the respondent's GPA is 3.62 approximately with a standard deviation of 0.25. Conclusion: There is no statistically significant relationship between nutritional status and student achievement